Small perturbations in a finger-tapping task reveal inherent nonlinearities of the underlying error correction mechanism - Bavassi, Mariana Luz (2013)
Time estimation is critical for survival and control of a variety of behaviors, both in humans and other animals. Time processing in the few hundred milliseconds range, known as millisecond timing, is involved in motor control, speech generation and recognition, and sensorimotor synchronization like playing music or finger tapping to an external beat. In finger tapping, a mechanistic explanation in terms of neuronal activations of how the brain achieves average synchronization against inherent noise and perturbations in the stimulus sequence is still missing despite considerable research. In this work we show that nonlinear effects are important for the recovery of synchronization following a perturbation (a step change in stimulus period), even for perturbation magnitudes smaller than 10% of the period, which is well below the amount of perturbation needed to display other nonlinear effects like saturation. We build a mathematical model for the error correction mechanism and test its predictions, and further propose a framework that allows us to unify the description of the three common types of perturbations and all perturbation magnitudes with a single set of parameter values. While previous works have proposed that multiple mechanisms/strategies are used for correcting different perturbation conditions (based on fitting the model?s parameters separately to different perturbation types and sizes), our results suggest that the synchronization behavior can be interpreted as the outcome of a single mechanism/strategy, and call for a revision of the idea of multiple strategies.